A Qualitative Exploratory Study into the experiences of UK nursing students who have participated in the Kulyaaba scheme, Zambia - Bryans, Elizabeth (2009)
The introduction of study abroad programmes to undergraduate nursing education in the UK has been a relatively new development and literature pertaining to this is therefore limited. A gap in knowledge is especially prominent where student perspectives are concerned. This research was designed to explore the experiences of nursing students who have participated in a popular study abroad programme, Kulyaaba. The question asked was ‘How does participation in Kulyaaba impact the lives of nursing students who experience the phenomenon?’